2007
DOI: 10.1007/s10404-007-0232-x
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic analysis of CO2 bubble dynamics using thermal lattice-Boltzmann method

Abstract: By means of microfluidic analysis with a thermal lattice-Boltzmann method, we investigated the hydrophilic, thermal and geometric effects on the dynamics of CO 2 bubbles at anode microchannels (e.g., porous layers and flow channels) of a micro-direct methanol fuel cell. The simulation results show that a more hydrophilic wall provides an additional attractive force to the aqueous methanol in the flow direction and that moves the CO 2 bubble more easily. The bubble propagates quicker in the microchannel with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Values of contact angles used in simulation match closely water/PEO and water/polycarbonate static contact angles verified through numerical calibration. Investigation of wall wettability on the two-phase flow using the LBM modeling method was also previously conducted by Fei et al 23 Properties of species, water and air, as well as their interactions with solids were adopted from Huang et al 21 In all cases, when a liquid film was initialized between the bubble and channel wall, Eq. 6 was used based on a relation provide by Aussillous and Qu er e. …”
Section: Methodsmentioning
confidence: 99%
“…Values of contact angles used in simulation match closely water/PEO and water/polycarbonate static contact angles verified through numerical calibration. Investigation of wall wettability on the two-phase flow using the LBM modeling method was also previously conducted by Fei et al 23 Properties of species, water and air, as well as their interactions with solids were adopted from Huang et al 21 In all cases, when a liquid film was initialized between the bubble and channel wall, Eq. 6 was used based on a relation provide by Aussillous and Qu er e. …”
Section: Methodsmentioning
confidence: 99%
“…Fei et al (2006) and Fei and Hong (2007) investigated the bubble transport in a micronsized channel by a 2D LB method. In a follow-up paper, they studied heat transfer including Marangoni effects due to a temperature dependent surface tension and found that bubbles moved more rapidly in a divergent microchannel than in a straight or convergent channel (Fei et al 2008). …”
Section: Marangoni Effects and Surfactantsmentioning
confidence: 97%
“…Oscillation of two-phase flow in microchannels for cooling applications was studied and a control method by using an adjustable inlet orifice was presented [26]. The studies of bubble dynamics in the microfluidic circumstances with numerical methods were also suggested [27,28]. Some other properties of the gas-liquid two-phase flow in microchannels were studied under different circumstances [29,30].…”
Section: Introductionmentioning
confidence: 98%